2006
DOI: 10.1124/jpet.105.098517
|View full text |Cite
|
Sign up to set email alerts
|

2-(1-Hydroxypentyl)-benzoate Increases Cerebral Blood Flow and Reduces Infarct Volume in Rats Model of Transient Focal Cerebral Ischemia

Abstract: 2-(1-Hydroxypentyl)-benzoate (dl-PHPB), a derivate of 3-n-butylphthalide (dl-NBP), is a novel drug candidate used for treatment of cerebral ischemia. The goal of the present study was to investigate the effects of dl-PHPB on infarct volume, neurological function, and cerebral blood flow (CBF) in transient focal cerebral ischemia. Therefore, an animal model of 2-h middle cerebral artery occlusion (MCAO) followed by 24-h reperfusion was used. Rats received dl-PHPB (1.3, 3.9, or 12.9 mg/kg) intravenously 10 min a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 24 publications
0
64
0
1
Order By: Relevance
“…NBP exhibits protective effects against focal cerebral ischemia in animal models through the prevention of mitochondrial damage, the inhibition of neuronal apoptosis, the improvement of cerebral blood flow, and the reduction of infarct volume [21,22,23]. Our previous studies demonstrated that NBP could significantly inhibit caspase-3-mediated apoptosis after cerebral ischemia in diabetic rats [24]; and NBP administration could attenuate stroke-induced neuron loss and activation of astrocytes in diabetic rats [25].…”
Section: Discussionmentioning
confidence: 99%
“…NBP exhibits protective effects against focal cerebral ischemia in animal models through the prevention of mitochondrial damage, the inhibition of neuronal apoptosis, the improvement of cerebral blood flow, and the reduction of infarct volume [21,22,23]. Our previous studies demonstrated that NBP could significantly inhibit caspase-3-mediated apoptosis after cerebral ischemia in diabetic rats [24]; and NBP administration could attenuate stroke-induced neuron loss and activation of astrocytes in diabetic rats [25].…”
Section: Discussionmentioning
confidence: 99%
“…The parietal cortical perfusion in the territory of MCA was measured. The laser Doppler probe was connected to a BLF21D laser Doppler flowmeter (Transonic systems Inc., Ithaca, NY, USA), and the values were obtained from 10 min before the ischemic event until 15 min after reperfusion 28) . The changes in rCBF are expressed as the percentage of the baseline values.…”
Section: Regional Cerebral Blood Flowmentioning
confidence: 99%
“…Five minutes after the pMCAO operation, the probe was inserted again to monitor rCBF, showing a sharp drop of rCBF (approximately 5%-10% of the pre-ischemia value). Then the rCBF was measured again 15, 30 and 60 min after surgical operation [15] . Evaluation of infarct volume, brain water content and neurological deficit Twenty-four hours after ischemia, the neurological deficits in rats subjected to pMCAO were evaluated using a protocol previously described in a blinded manner [16] .…”
Section: Animal Preparation and Experimental Protocolmentioning
confidence: 99%